A Big-Data Approach to Contemporary French Politics. - Sobanet, Andrew; Singh, Lisa (Contemporary French & Francophone Studies, 2020)
Mixing the methods of machine learning and those of French cultural studies, this article explores recent trends in French politics. We analyze a large data set from Twitter (over a hundred and fifty million tweets) in order to reveal notable currents in discourse around the Gilets Jaunes and the French presidency (with particular focus on Emmanuel Macron and Marine Le Pen). This article delineates our methods and places this data analysis in a broader cultural and political context, concentrating primarily on major trends in French politics from 2017 to late 2019. We argue that our interdisciplinary approach reveals elements of French political discourse that would otherwise remain obscure, especially regarding the rise and fall of the Gilets Jaunes movement on Twitter.